Optimal PV Generation Using Symbiotic Organisms Search Optimization Algorithm-Based MPPT - (:unkn) unknown (IEEE, 2020)
In this period when the technology has been developing rapidly, resources are being exhausted as well conversely. Therefore, possible problems and the ways of handling them are changing and new problem-solving techniques are being tried. Due to the intermittent nature of photovoltaic (PV) systems, which have solar irradiance and temperature as a source, the problem of maximum power attaining arises. The solution to this problem aims to make optimal use of PV energy production. This study presents a metaheuristic algorithm to solve the problem of maximum power point tracking (MPPT) from PV systems which are an indispensable part of renewable energy technology. Symbiotic organisms search (SOS), a powerful and dynamic metaheuristic optimization algorithm, is adopted as a solution to this problem. The SOS algorithm has been inspired by the symbiotic interactions adopted their behavior to survive in the ecosystem, which has developed to solve optimization and engineering problems. The proposed algorithm, i.e., SOS, has been embedded in MATLAB/Simulink platform to test for accuracy and efficiency. From the obtained results, this evolutionary SOS algorithm is seen obviously to outperform in certain points more than the classical Perturb and Observe (P&O) and Incremental Conductance (INC) methods for the same system and conditions.
Keywords: Power Point Tracking (MPPT); Photovoltaic (PV); Symbiotic Organisms Search (SOS) Algorithm; Optimization